Local Tourist favored Tanah Lot as a place to visit after COVID-19 lockdown - Ida Ayu Agung Adnyawati (Bali Tourism Journal, 2020)
Tabanan Regent Ni Putu Eka Wiryastuti reopened five tourist attractions in Tabanan district closed since 22 March 2020 due to the Covid-19 pandemic. Those Tourist attractions were Tanah Lot, Ulundanu Temple, Eka Karya Botanical Garden Bedugul, The Blooms Garden Baturiti, and Jatiluwih, Penebel. She explained the decision was urgently needed to resurrect economic activity in Tabanan district in the new normal phase.1 Since the reopening day, domestic tourists flooded Tanah Lot, Tabanan. The number of visits had skyrocketed, starting from 20 July to 22 August 2020. As one of Bali's leading preferable tourist destinations, Tanah lot offers majestic landscapes and historical value that should not be missed. Established in the 16th century, Tanah Lot is a temple for lord of the sea, after a priest named Dang Hyang nirartha received revelation on a vast reef at the beraban village coast. Later, Tanah lot is considered a holy site and a favorite landmark for tourism. COVID-19 outbreak forced the local Government to close most public places on the island. On 20 July 2020, Tabanan regent decided to reopen five out of many tourism objects in its area, including the coastal landmark. Since reopening, its number of visits spiked rapidly, over twenty thousand visits in less than a month. Despite its huge demand, it did not significantly impact the economic atmosphere around the area. The management explained that the hawkers believed tourist visits were relatively low compared to before the pandemic. They argued the visitor purchasing power might also go down. The other reasons were that some stall owners terminated their contracts, and some preferred to sell from their homes.